Utilization and adherence to guideline-recommended lipid-lowering therapy at an academic medical center - Khalid A. Alburikan; Rayah M. Asiri; Abduallah M. Alhammad; Amer A. Abuelizz; Ghada A. Bawazeer; Mohammed H. Aljawadi (Annals of Saudi Medicine, 2017)
BACKGROUND: Clinical guidelines for managing blood cholesterol were updated in November 2013. OBJECTIVE: To evaluate the adherence to the 2013 American College of Cardiology/American Heart Association (ACC/AHA) guideline recommendations for statin therapy in the treatment of elevated blood cholesterol in high-risk patients. DESIGN: A single-center, retrospective, observational study. SETTING: A tertiary care academic medical center in Riyadh, Saudi Arabia. PATIENTS: Consecutive adult patients discharged with a prescription for any of the statin medications group between 1 June 2015 and 31 December 2015. MAIN OUTCOME MEASURE(S): Adherence to the 2013 ACC/AHA guidelines for management of cholesterol by statin therapy in high-risk patients. RESULTS: Of 1094 patients, 753 (68.8%) met the inclusion criteria of the study. Of these 753 patients, 53.5% had atherosclerotic cardiovascular diseases; 29.2% had diabetes; 0.9% had an LDL-C level >190 mg/dL; 10.8% had an estimated 10-year risk >7.5%; and 4.9% had no risk. Two hundred and eight (27.6%) patients received statin therapy at an inappropriate intensity according to their risk group based on the guideline; 126 (16.7%) received less than the ideal intensity. CONCLUSION: Approximately one-third of patients received statin therapy at an inappropriate intensity according to the guideline recommendation. Wide application of the 2013 ACC/AHA cholesterol guidelines in our practice would optimize the utilization of statin therapy at the ideal intensity in high-risk patients. LIMITATION: Drug-drug interactions and intolerance to statin therapy were not considered when we evaluated adherence among high-risk patients.